Gray Matter Atrophy within the Default Mode Network of Fibromyalgia: A Meta-Analysis of Voxel-Based Morphometry Studies. (26th December 2016) - Lin, Chemin; Lee, Shwu-Hua; Weng, Hsu-Huei
Abstract : Over the years, studies have demonstrated morphological changes in the brain of fibromyalgia (FMS). We aimed to conduct a coordinate-based meta-analytic research through systemic review on voxel-based morphometry (VBM) imaging results to identify consistent gray matter (GM) difference between FMS patients and healthy subjects. We performed a comprehensive literature search in PubMed (January 2000–December 2015) and included six VBM publication on FMS. Stereotactic data were extracted from 180 patients of FMS and 123 healthy controls. By means of activation likelihood estimation (ALE) technique, regional GM reduction in left medial prefrontal cortex and right dorsal posterior cingulate cortex was identified. Both regions are within the default mode network. In conclusion, the gray matter deficit is related to the both affective and nonaffective components of pain processing. This result also provided the neuroanatomical correlates for emotional and cognitive symptoms in FMS.